The returns to temporary migration: The case of Italian Ph.D.s - Marco Di Cintio; Emanuele Grassi (Economics and Econometrics Research Institute (EERI), 2016)
This paper examines the implications of temporary migration episodes for two cohorts of Italian Ph.D.s. Special attention is given to the duration of experience abroad, its contribution to earned wages and the selectivity of returnees. After controlling for the endogeneity of both the migration decision and the length of stay abroad, we find positive returns to longer periods abroad and negative returns to shorter periods. Returnees are also found to be positively self-selected. The results are confirmed in several robustness and sensitivity checks.
Keywords: J3; J61; F22; 330; skilled migration; return migration; migration premium; self-selection